AKHIR ZAMAN MENURUT SURAT 1 TESALONIKA: SEBUAH ANALISA TEOLOGIS-PRAKTIS - Oet, Supriadi (Manna Rafflesia, 2014)
The end of time is the subject of much interest today. Then many responses to the end times appear, but those responses tend to lead believers to be passive in this life. A biblical study is needed to understand the end of time. Because not all concepts of the end times make Believers understand how the end times really are. In the midst of the many teaching concepts about the end times, many theologians have also forgotten to give practical applications in dealing with the end times. Through this article, it is hoped that this will help Christians to understand what is the end of time based on 1 Thessalonians and how to deal with it practically.